Endodontic Reintervention Of The Maxillary First Premolar: A Case Report - Hikmah, Noor; Kosi, Rina (Journal of Case Reports in Dental Medicine, 2021)
Objective: This case report describes an endodontic reintervention of the maxillary premolar teeth.Methods: A 57-year-old female patient came to RSGMP UNHAS with complained of pain in maxillary teeth when chewing or biting has been felt since the last 1 month. This tooth was treated about 2 years ago. On clinical examination, there was a fracture composite restoration. Radiographs revealed inadequate root canal obturation and periapical radiolucency. Based on subjective and objective examination the dental diagnosis was previously treated. radiolucency. Based on subjective and objective examination the dental diagnosis was previously treated.Result: After treatment, the subjective and objective complaints of the patient have disappeared and when control is carried out one year after treatment it appears on the radiological picture the lesion has improved.Conclusion: Endodontic reintervention is an effective alternative that can be done to treat endodontic failure.